Synthesis and mesomorphic properties of novel bent-shaped naphthyl diketones - Buljan, Anđela, inženjerka kemije (Array, 2019)
The synthesis and liquid-crystalline properties are reported for novel naphthyl-based diketones incorporating variant terminal chains and lateral fluoro- substitution. Newly prepared materials exhibit a broad temperature range of the nematic phase. The study demonstrates how subtle structural modifications can be exploited to alter the efficiency of molecular packing and consequently the thermal behaviour.